The Effect of Copper and Tungsten Addition of the Passivity and Pitting Corrosion Resistance of Super Duplex Stainless Steels - EDWARD PURKHARDT (2024)
The Critical Pitting Temperatures of Ferralium 255 (UNS S32550), Zeron 100 (UNS S32760), and SAF2507 (UNS S32750). were investigated to look at the effect of pH on the measured critical pitting temperature (CPT)and to understand the type of mechanism driving the formation and growth of the pits.Due to the elevated copper concentration in Ferralium alloy compared to the other alloys and, the elevated tungsten concentration in the SAF2507 (SAF)alloy compared to the alloys. The effect of copper and tungsten addition on the measured CPT could also be investigated.An investigation into the effect of the pH of the test solution on the three alloys was conducted. All three alloys underwent a CPT test sweep at 4pH, 7pH and 10pH.A clear difference was measured in the CPT of the individual alloys, they all had a measurable and notable difference in measured breakdown temperature.his consisted of the copper rich alloy (Ferralium) having an average CPT of 76oC across the three tested pH solutions. The low copper alloy (Zeron) having the next highest measured CPT of 85oC. With the tungsten rich alloy (SAF)having the highest measured CPT of 89oC.SEM imaging of the pits that formed found that the pits that had formed in all of the CPT sweeps for all of the alloys had formed a pit structure known as lacy capped pits. This cap on the pit is likely to enable concentrations of the solution on the internal of the pit to be high enough to encourage corrosion of the highly corrosion resistance super duplex stainless steels. There is no visible difference in the structure of the lacy capped pit formed in the individual alloys.Time-lapse imagery (TLI) of the samples undergoing CPT sweeps was conducted to confirm that the pits were forming after the alloy transitioned through its critical temperature. The measured CPT of the individual alloys were consistent with those measured in the previous 3 investigations. The TLI was able to capture the formations of the pits as the material transitioned through its critical temperature. It is possible that re-passivation of the pits were captured in the TLI. The re-passivation is likely to be caused by the lacy caps of the pits being removed or degrading. The loss of the cap results in the internal environment of the pit to no-longer be conducive to continuation of the corrosion reaction.